2005
DOI: 10.1002/nme.1345
|View full text |Cite
|
Sign up to set email alerts
|

A new formulation of Signorini's type for seepage problems with free surfaces

Abstract: SUMMARYA new variational inequality formulation for seepage problems with free surfaces is presented, in which a boundary condition of Signorini's type is prescribed over the potential seepage surfaces. This makes the singularity of seepage points eliminated and the location of seepage points determined easily. Compared to other variational formulations, the proposed formulation can effectively overcome the mesh dependency and significantly improve the numerical stability. A very challenging engineering exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 17 publications
0
43
0
5
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 w ℓ is illustrated with black arrows indicating the change on liquid velocity. The solution in [9] is highlighted in green while the solution by this paper is highlighted in light blue. We can observe that the final phreatic line matches fairly well the reference one, even though the liquid retention model is not as discrete as in the reference work.…”
Section: Example 3: Embankment Dammentioning
confidence: 99%
See 3 more Smart Citations
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 w ℓ is illustrated with black arrows indicating the change on liquid velocity. The solution in [9] is highlighted in green while the solution by this paper is highlighted in light blue. We can observe that the final phreatic line matches fairly well the reference one, even though the liquid retention model is not as discrete as in the reference work.…”
Section: Example 3: Embankment Dammentioning
confidence: 99%
“…24 where it can be observed that the pressure-saturation distribution at the end is similar to the distribution obtained in Example 1. 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 The reference line is shown in green with square markers [9]. Arrows...…”
Section: Example 4: Wetting Of Unsaturated Rectangular Porous Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…Они се формирају уз помоћ стварне геометрије објекта и стварних карактеристика материјала и калибришу се према реалним мерењима [3]. Главне врсте таквих модела које се користе у анализи стања брана су филтрациони [4][5][6] и напонско-деформациони модели [7]. Дивац и сар.…”
Section: уводunclassified